(untitled) (Lundiana: International Journal of Biodiversity, 2003)
The difference in treatment of vocal features in Oscines and Suboscines passerine birds characterizes a large portion of the current studies on their taxonomy. In the former taxon, vocalization is supposed to be molded by learning, and consequently is not regarded as taxonomically informative. In the latter, a strong emphasis is given to vocalization because it supposedly reflects the genetic structure of populations. This paper reviews the various assumptions related to this difference in treatment, including the overestimation of the vocal characters in suboscine alpha taxonomy due to the alleged importance of vocalization under the framework of the species mate recognition system. The innate origin of suboscine vocalizations remains to be rigorously demonstrated and the use of vocalization as “super-characters” is prejudicial to bird taxonomy. Despite the possibility of being learned, vocalization should also be used in the taxonomic studies of oscine passerines.